2019
DOI: 10.1021/acs.jafc.8b07248
|View full text |Cite
|
Sign up to set email alerts
|

Role of Theobromine in Cocoa’s Metabolic Properties in Healthy Rats

Abstract: Cocoa is rich in polyphenols and methylxanthines and it has been reported that its consumption, among other properties, has beneficial effects on metabolism. This study aimed to investigate the role of theobromine in cocoa's metabolic properties in healthy rats. In addition to morphometric measurements, biochemical markers of lipids and glucose metabolism and gene expression of molecules related to immune cells in adipose and hepatic tissues were assessed after 7 or 18 days of diet. Additionally, a metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
0
18
1
Order By: Relevance
“…Moreover, the anti-obesity potential of cocoa has already been discussed in several reviews ( 21 , 71 73 ). Although we previously attributed the lower BW gain of rats fed with cocoa to the impact of theobromine and flavonoids on lipid and glucose metabolism, fat deposition and even the gut microbiota composition ( 22 , 74 ), the current results suggest that a decrease in FFAR3 intestinal expression may also contribute to this multifactorial effect.…”
Section: Discussioncontrasting
confidence: 69%
“…Moreover, the anti-obesity potential of cocoa has already been discussed in several reviews ( 21 , 71 73 ). Although we previously attributed the lower BW gain of rats fed with cocoa to the impact of theobromine and flavonoids on lipid and glucose metabolism, fat deposition and even the gut microbiota composition ( 22 , 74 ), the current results suggest that a decrease in FFAR3 intestinal expression may also contribute to this multifactorial effect.…”
Section: Discussioncontrasting
confidence: 69%
“…Indeed, previous studies in animals have shown that cocoa supplementation counteracts the effects of diets high in fat, preventing weight gain and total fat mass increase, by modulating lipid metabolism [26][27][28] . The effect of cocoa on body composition in a healthy animal model has been addressed very recently and showed that cocoa decreased body mass, BMI, Lee's index (which evaluates the degree of obesity) and retroperitoneal fat content 29 . The positive effects of cocoa on body composition are believed to be attributed to its flavanols content, particularly the monomeric flavanol epicatechin 30 , because of its high bioavailability and potential to exert systemic effects 31 .…”
Section: Discussionmentioning
confidence: 99%
“…While caffeine is able to inhibit the expression of tumour necrosis factor (TNF)-α by suppressing the cyclic-adenosine monophosphate/protein kinase A (cAMP/PKA) pathway and inhibiting cAMP phosphodiesterase ( Horrigan, Kelly & Connor, 2004 ) no variation in the production of IL-1β, IL-12 and IL-10 has been observed in human studies ( Horrigan, Kelly & Connor, 2004 ; Loftfield et al, 2015 ; Haskó & Cronstein, 2011 ). In the case of theobromine, a decrease in IL-1β levels was reported in studies conducted in vitro ( Fuggetta et al, 2019 ) and in mice ( Camps-Bossacoma et al, 2019 ). In contrast, in humans, no studies with theobromine and inflammatory markers other than C-reactive protein (CRP) were found.…”
Section: Resultsmentioning
confidence: 91%